Enhancement of voltage profile by incorporation of SVC in power system networks by using optimal load flow method in MATLAB/Simulink environments. (November 2018) - Singh, Bindeshwar; Agrawal, Garima
Abstract: Flexible AC Transmission Systems (FACTS) controllers could be a suitable alternative to provide reactive power support at the load centers locally and hence keep the voltages within their safe operating limits. Due to high costs of FACTS devices, their proper location in the system must be ascertained. The fundamental object of this thesis work is to improve the voltage profile by reducing the real and reactive power loss in the system. The voltage profile in the system is being improved by using the FACTS device Static VAR Compensator (SVC). In this paper, studies and analyzes SVC technology for voltage enhancement, reducing system losses, suppression of fluctuations. The effectiveness of the proposed method has been tested on IEEE-9 and IEEE-30 bus systems. Optimal placement has been obtained for the base case loading and to verify its locations. To achieves the optimization of the location and the size of the power system to optimize the system performance. A Newton–Raphson Load Flow problem has been formulated with an objective to improve the voltage profile with minimization of the losses. Moreover, the effects of SVC on economic condition have also been investigated. The results obtaining is in the form of the plot and compared with the plots without SVC. This work also helpful for whose persons are working in the field of FACTS controllers planning.